2001
DOI: 10.1006/viro.2001.1130
|View full text |Cite
|
Sign up to set email alerts
|

Truncation of the Human Adenovirus Type 5 L4 33-kDa Protein: Evidence for an Essential Role of the Carboxy-Terminus in the Viral Infectious Cycle

Abstract: The subgroup C human adenovirus L4 33-kDa protein is a nuclear phosphoprotein that plays a direct, but dispensable, role in virion assembly. The r-strand open reading frame (ORF) for this protein lies opposite to the 5' end of the l-strand E2 early (E2E) transcription units. To facilitate studies of regulation of E2E transcription, we wished to construct a mutant virus in which the 33-kDa ORF was truncated to serve as a background into which specific E2E mutations could be introduced without also altering the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 81 publications
4
38
2
Order By: Relevance
“…Alternatively, Finnen et al suggested that their truncation may have created a dominant-negative form of the protein (14). However, both studies point to a role for 33K in the assembly of particles, whereas data presented here show that 33K is required to turn on full late gene expression.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Alternatively, Finnen et al suggested that their truncation may have created a dominant-negative form of the protein (14). However, both studies point to a role for 33K in the assembly of particles, whereas data presented here show that 33K is required to turn on full late gene expression.…”
Section: Discussioncontrasting
confidence: 52%
“…Of the three studies, only the present one unambiguously examined the effect of a total lack of 33K; the other two retained substantial parts of the 33K reading frame. According to this reasoning, the central part of 33K, deleted here but retained and potentially expressed in the studies of Fessler and Young and of Finnen et al (13,14), would be necessary and sufficient for regulating the MLTU switch. Alternatively, the primary function of 33K may be in activating late gene expression, leading secondarily to defective assembly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7B). The second paper introduced two tandem translational stop codons in the conserved carboxy-terminal part of L4-33K (30). This mutation was lethal.…”
Section: Discussionmentioning
confidence: 99%
“…Following digestion with PacI (New England BioLabs), the released viral genome was isolated using the Qiaex II kit (Qiagen) following electrophoresis in 0.75% low-meltingpoint agarose (International Biotechnologies Inc.). To isolate dl341 DNA, 293 cells at 90% confluence were infected with 5 PFU/cell of the mutant for 44 h, and virus particles were isolated by sequential sedimentation in CsCl step and continuous gradients as described previously (87). Viral DNA was purified from the particles following dialysis into 0.01 M TrisHCl, pH 7.5, containing 1 mM EDTA as described previously (88).…”
Section: Cells and Virusesmentioning
confidence: 99%